Rapid detection of Newcastle disease virus (NDV) with SYBR Green I real-time polymerase chain reaction - Tan, Sheau Wei; Ideris, Aini; Omar, Abdul Rahman; Mohd Yusoff, Khatijah; Tan, Wen Siang (Universiti Putra Malaysia Press, 2004)
A two-step real-time PCR assay for the detection of Newcastle disease virus (NDV) was developed. Twelve NDV isolates (7 velogenic, 1 mesogenic and 4 lentogenic strains) were used. All the isolates showed positive results in amplification. Specificity of the amplification was confirmed by melting curve analysis. The melting temperatures (Tm) of all the isolates were between 86ºC to 87ºC. No primer dimer and non-specific products were detected during the amplification. A serial 10-fold dilution of cDNA was carried out to determine the sensitivity of the assay. In the optimal conditions, the detection limit of the real-time PCR was 10 pg whereas, the RT-nested ELISA PCR and conventional PCR can only detect up to 1 ng and 10 ng, respectively. Thus, SYBR Green I based real-time PCR assay offers a sensitive, rapid and convenient method in diagnosing NDV.